Studium syntézy 3'-deoxy-3'-[18F]fluorothymidinu - perspektivního radiofarmaka pro pozitronovou emisní tomografii - Procházka, Libor; Kropáček, Martin; Mirzajevová, Marcela; Zimová, Jana; Försterová, Michaela; Švecová, Helena; Melichar, František (Chemické listy, 2008)
18F-Labelled compounds as active substances of radiopharmaceuticals are used for imaging in positron emission tomography (PET) in nuclear medicine. The radiosynthesis of PET radiopharmaceuticals is based on nucleophilic substitution with F- in a precursor. The synthesis is demonstrated on 3?-deoxy-3?-[18F]fluorothymidine.
Keywords: Dideoxynucleosides; financování organizované; Radiopharmaceuticals; radiofarmaka; Financing, Organized; pozitronová emisní tomografie; Thymidine; thymidin; dideoxynukleosidy; Positron-Emission Tomography